Morfometryczna analiza miesni ciezarowców - Cabric, M. (Sport wyczynowy, 2002)
Introduction. Although numerous quantitative analyses have been performed on the changes which occur in skeletal muscles following compensatory or work-induced hypertrophy in both animals and in man, surprisingly little detailed information is available on either muscle capillaries or myonuclei for human muscle. The purpose of this study was to analyze the capillary network, mitochondrial contents, the sizes of myonuclei, and their chromatin patterns. Material and methods. Muscle biopsies were obtained from the vastus lateralis muscles of five national-class weight-lifters, and also from five age-matched control subjects. The selected parameters were measured primarily by stereological techniques. Results and conclusions. Differences were noted in nuclear size, number of nuclei per unit area, length of nuclei, nuclear chromatin patterns, and differences in mitochondrial volume fractions in type II fibres.